INTEGRASI DEEP LEARNING DAN PENDEKATAN KONTRUKTIVISME UNTUK PENGUATAN KARAKTER ISLAMI DI ERA PEMBELAJARAN ABAD 21 - Azura, Yuni; Thoyib, Hadi; Meilinda, Yulia; Fransiska, Iit; Munawwaroh, Saidatul (JURNAL PENDIDIKAN DASAR, 2025)
Abstract: The purpose of this study is to examine the integration of deep learning and constructivism, which in this study is defined as deep learning that emphasizes conceptual understanding, active student involvement, and reflection on learning experiences, in improving vocabulary comprehension while supporting the strengthening of students' Islamic character, such as discipline, responsibility, and honesty, in the context of 21st-century learning. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The main data sources were third-grade students and classroom teachers. The results showed an increase in student active engagement, strengthening of vocabulary understanding through visual-interactive learning experiences, and changes in learning behavior that reflected deep learning, marked by increased discipline, responsibility, and honesty among students in the learning process. This study contributes by offering an alternative 21st-century learning model that is relevant to Islamic-based elementary schools and can be a reference for teachers in designing innovative, meaningful learning in line with digital technology developments and character-building needs. Keywords: Deep Learning, Constructivism, Islamic Character   Abstrak: Tujuan penelitian ini adalah untuk mengkaji integrasi deep learning dan pendekatan konstruktivisme, yang dalam penelitian ini dimaknai sebagai pembelajaran mendalam yang menekankan pemahaman konseptual, keterlibatan aktif siswa, serta refleksi terhadap pengalaman belajar, dalam meningkatkan pemahaman kosakata sekaligus mendukung penguatan karakter Islami siswa, seperti kedisiplinan, tanggung jawab, dan kejujuran, pada konteks pembelajaran abad ke-21. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Sumber data utama berasal dari siswa kelas III dan guru kelas. Hasil penelitian menunjukkan adanya peningkatan keterlibatan aktif siswa, penguatan pemahaman kosakata melalui pengalaman belajar visual-interaktif, serta perubahan perilaku belajar yang mencerminkan pembelajaran mendalam, ditandai dengan meningkatnya kedisiplinan, tanggung jawab, dan kejujuran siswa dalam proses pembelajaran. Penelitian ini berkontribusi menawarkan model alternatif pembelajaran abad ke-21 yang relevan bagi sekolah dasar berbasis Islam serta dapat menjadi rujukan bagi guru dalam merancang pembelajaran yang inovatif, bermakna sesuai dengan perkembangan teknologi digital serta kebutuhan penguatan karakter. Kata Kunci: Deep Learning, Konstruktivisme, Karakter Islami